2002
DOI: 10.1002/elps.200290034
|View full text |Cite
|
Sign up to set email alerts
|

Gerbils of a seizure‐sensitive strain have a mitochondrial inner membrane protein with different isoelectric points from those of a seizure‐resistant strain

Abstract: The distribution of proteins in the cerebral cortex of a seizure-sensitive (SS) strain of gerbil and its seizure-resistant (SR) counterpart was profiled using two-dimensional gel electrophoresis. A series of proteins of similar molecular weight (around 83 kDa) showed small but consistent differences in their isoelectric point (pI) with indistinguishable profiles of distribution between the two strains. Amino acid sequences of peptides produced by limited proteolysis of each protein in the spots from the strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Only a few studies reported the potential cause about the shift of isoelectric points for mitofilin potential modifications. Omori et al proposed that alternative splicing was involved in consistent differences in the isoelectric point for mitofilin in the cerebral cortex between seizure-sensitive gerbil and seizure-resistant gerbil [35].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies reported the potential cause about the shift of isoelectric points for mitofilin potential modifications. Omori et al proposed that alternative splicing was involved in consistent differences in the isoelectric point for mitofilin in the cerebral cortex between seizure-sensitive gerbil and seizure-resistant gerbil [35].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies suggest that mitofilin is an indispensable part of intramitochondrial morphogenetic machinery. Comparative proteomic analysis of the cerebral cortex of a seizuresensitive strain of gerbil and its seizure-resistant (SR) counterpart revealed that gerbil mitofilin showed consistent differences in their isoelectric point between the two strains (Omori et al, 2002). Sequence analysis of mitofilin cDNAs showed several mutations in the SR strains, including one that resides within a conserved region immediately carboxyl terminal of the membrane-anchoring domain.…”
Section: Discussionmentioning
confidence: 99%
“…To partially digest the NqrA subunit labeled by PUQ-3, the CBB-stained NqrA band was treated with V8-protease (Roche Applied Science, Penzberg, Germany) in a 15% Tris-EDTA mapping gel using according to the procedures described previously (32)(33)(34). The partial digests were characterized by mass spectrometry or N-terminal sequence analysis.…”
Section: Proteomic Analysismentioning
confidence: 99%